Wear Resistance Improvement in the Friction Wedge - Friction Plate Pair of a Freight Car Bogie Wedge-Type Shock Absorber - A. V. Sukhov; B. V. Borsch; A. V. Gabetz (Вестник Научно-исследовательского института железнодорожного транспорта, 2015)
Low wear resistance in the friction pair friction wedge - friction plate proves to be the key reason for insufficient operational workability of the wedge-type shock absorber of a freight car bogie swing suspension. The authors come up with the problem solution consisting in application of new materials for the indicated friction pair, specifically grade ChMN-35M alloyed iron for friction wedge and grade 25Kh steel for friction plate. To assess wear resistance of the selected materials there was conducted JSC VNIIZhT based research and testing campaign comprising comparative testing of material samples on the friction and wear machine MI-1 (Amsler tests), full-scale tests of friction wedges and plates on the type TsDM 200 Pu testing rig and tests of friction wedges and plates in trial runs over the experimental loop track. Outcomes analysis of the rig tests and trial runs campaign with sample parts fabricated of the indicated materials al-lowed to prove their higher wear resistance as compared with mass production parts in terms of ensuring the required service life of the wedge-type shock absorber. Comparative outcomes analysis of the experiments conducted to assess wear resistance of the selected friction pairs demonstrates that with the specified service life indice performance of rig tests only is just enough to determine the amount of contacting surfaces wear of the examined materials and to arrive at a preliminary decision on the materials to be used for friction parts of the freight car bogie wedge-type shock absorber.